Institutionalization of Religion in Schools to Intercultural Education - Casey, Erin; Kudeva, Rumyana; Rousson, Ashley (Jurnal Ilmiah Peuradeun, 2018)
Education is closely associated with religion. Education is the doctrine of morals and intelligence of the mind and religion is belief in God with the teachings of worship and obligations. Religion prepares a comprehensive norm that underlies life educational purposes. Educational institutions have played their significant part in the production and reproduction of European warfare. Nationalist curricula in history, national language and literature, social sciences and religion typify many school systems. Educational institutions are theoretically the opposition to those of religion: critical exegesis of all texts and the subjection of all theories to rigorous attempts at falsification are the commonplace expectations of educational institutions. All too often, however, religious organizations are actually in charge of schools and even universities. Of course state sponsored educational systems have other objectives, which take precedence over the pursuit of knowledge, in particular social control and nation building. It is in these two areas that the alliance between church and state in the control of the reproduction of knowledge is at its most symbiotic. Schools and universities, ostensibly the key intuitions of modernization and modernity, are in actuality one of the main sites for the production and reproduction of religion.